Pariwisata Indonesia dalam Citra Mooi Indie: Dahulu dan Sekarang - Sandang, Yesaya; Sanjaya, Rindo Bagus (Universitas Kristen Satya Wacana, 2017)
From time to time Indonesia tourism image has been evolving and influnced by many factors. However since the colonial era, Indonesia tourism image has been designed in terms of Mooi Indie, and although the image it self already evolving, the terms of Mooi Indie stays in debate. This article tries to argue despite the pro and contra about the bad impact of tourism in terms of Mooi Indie, there are some differences between Mooi Indie in past and present time. Under the current development of tourism paradigm in the world as well in Indonesia, there are new hopes for overcoming bad impacts brought by tourism activities. In the end, Indonesia tourism image will always remain in tension between what is beautiful and the what’s in the reality. Thus, Mooi Indie can not be allowed an understood as the only image and tools to produce tourism reality, but rather as a critisism and motivation to achive the ultime goal of tourism in Indonesia.